ANALYSIS OF SHARIA BANKING STRATEGIES IN FACING ECONOMIC CONSTRUCTION 5.0 REVIEWED THROUGH SWOT ANALYSIS (CASE STUDY BSI KCP ADAM MALIK) - Fadhila, Alya (Universitas Islam Lamongan, 2024)
SWOT analysis is the most commonly used analysis method in the industrial world to formulate strategies. In this research, SWOT analysis is used to understand the strengths, weaknesses, opportunities and threats faced by Islamic banks in the context of economic construction 5.0. This research aims to find out how to apply SWOT analysis in strategy. Marketing can help Islamic banks to strategies can help Islamic banks to compete in a competitive banking market. Sharia banks can implement several strategies, such as market penetration, developing competitive and innovative sharia banking products, improving service quality, increasing promotion and socialization of sharia banking products, strengthening cooperation with other organizational institutions, expanding the sharia bank office network, increasing market coverage through analysis. strategy, and improving the quality of human resources. This method uses a qualitative descriptive approach. Descriptive qualitative research is research that uses words or images obtained from interviews in the form of notes, personal documents, recordings or other documents. compete in the competitive banking market. The research results show that sharia banks have strengths such as market penetration, development of competitive and innovative sharia banking products, improving service quality, increasing promotion and socialization of sharia banking products, strengthening cooperation with other organizational institutions, expanding the sharia bank office network, increasing market coverage through strategic alliances, and improving the quality of